1944
DOI: 10.2307/4079515
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Distribution of the Trematode, Collyriclum faba (Bremser) in Birds

Abstract: FARNER AND MORGAN, Collyriclum faba in Birds 't21 1944-s OCCURRENCE AND DISTRIBUTION OF THE TREMATODE, COLLYRICLUM FABA (BREMSER) IN BIRDS THE trematode, Collyriclum faba, has been reported from two orders, thirteen families, 24 genera, and 26 species of birds. This fluke occurs in cysts in the skin, primarily around the vent. The purpose of this paper is to record a new host occurrence, give a brief review of the literature, and present a complete parasite-host list with its geographical distribution. It is h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Only studies involving more than 100 birds examined or more than one bird infected are included in this table countries, whereas the vast sample of barn swallows and sand martins examined in the other Eurasian countries did not turn in any single positive finding, supporting the hypothesis claiming Central Europe to be the major area of C. faba occurrence in Europe. Somewhat controversial is, whether C. faba occurs more frequently in younger hosts as found by Jegen (1917), Riley (1931), Farner and Morgan (1944), Literák and Sitko (1997), and Literák et al (2003) who suggest that the pulli or juveniles are infected through the food brought to the nest by the parents. However, Blankespoor et al (1985) reported absence of C. faba cysts on nestlings and lower ratio of infected juveniles compared to adults.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Only studies involving more than 100 birds examined or more than one bird infected are included in this table countries, whereas the vast sample of barn swallows and sand martins examined in the other Eurasian countries did not turn in any single positive finding, supporting the hypothesis claiming Central Europe to be the major area of C. faba occurrence in Europe. Somewhat controversial is, whether C. faba occurs more frequently in younger hosts as found by Jegen (1917), Riley (1931), Farner and Morgan (1944), Literák and Sitko (1997), and Literák et al (2003) who suggest that the pulli or juveniles are infected through the food brought to the nest by the parents. However, Blankespoor et al (1985) reported absence of C. faba cysts on nestlings and lower ratio of infected juveniles compared to adults.…”
Section: Discussionmentioning
confidence: 94%
“…It has been suggested that the parasite is limited to certain geographical regions (Farner and Morgan 1944), which were thought to be restricted to Central Europe, Northeastern USA (MD, NJ, MA), and North Central USA (WI, MI, MN). However, later research confirmed that the species is distributed through Eurasia, from Kuril Islands to France, and through Americas, stretching from Massachusetts to California, and as far South as to Panama and Argentina (Sharpilo and Loskot 1967;Speich 1971;Stunkard 1971;Kirmse 1987;Literák et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It is now known that Tyzzer's examples were indeed C. faba, which parasitizes a very wide range of birds, mostly passerines but also domestic poultry (34,78,79), although its definitive life cycle remains unknown (31,64). Tyzzer provided a detailed description of the fluke, correcting and expanding observations of previous authors and paying special attention to the reproductive system, the fertilization process, and the development of the ova, which he suggested might be released from the parasitophorous cysts into the water when birds were bathing.…”
Section: Avian Diseasesmentioning
confidence: 99%
“…Collyriclum faba has been reported from many species of birds in Europe, Asia, and North, Central, and South America (Farner and Morgan, 1944;Stunkard, 1971;Kirmse, 1987;Literák et al, 2003;Literák and Sitko, 2006;Heneberg et al, 2011;Literák et al, 2011); it has never been reported from Africa before. At the place where the infected specimen was found, P. trochilus was not a breeding species, which meant that it was migrating from central/northern Europe to its winter quarters located in the central and southern parts of Africa (Moreau, 1972).…”
mentioning
confidence: 99%
“…The only available reports about the hosting of C. faba by a willow warbler dates from 8 June 1831 in southern Germany (Farner and Morgan, 1944) and from 15 May 1961 in the former Soviet Union (BykhovskayaPavlovskaya and Khotenovsky, 1964).…”
mentioning
confidence: 99%